Margalefidinium polykrikoides blooms and their impacts on fish mortalities in Malaysia Coastal - Mohammad Noor, Normawaty; Abdul Latif, Asilah Al-Has; Adam, Aimimuliani; Mustafa, Shuhadah; Mohd Razali, Roziawati (2023)
Harmful algal blooms (HABs) caused by the fish killer, Margalefidinium polykrikoides had expanded across Asia, North America and Europe and affected aquaculture, fishery and tourism industries. In Malaysia, the first occurrence of this species in coastal waters of Sabah was in 2005 and had caused loss up to RM 1 million to aquaculture industry. Since then, the bloom of this species has spread to many coastal areas in Malaysia causing devastating impacts. To decrease the impact, the Department of Fisheries Sabah (DOF) has performed monthly monitoring and come out with a strategy to safeguard community and aquaculture industry. Based on the monitoring from 2009-2022, several coastal areas in Sabah have higher frequency of M. polykrikoides occurrences. In this paper, the occurrences of M. polykrikoides at different coastal areas, the impacts and mitigation strategies will be discussed. This is important to ensure marine food industry is sustained to support rising human population and save the marine environment for future generation.